Do intestinal parasitic infestations in patients with clinically acute appendicitis increase the rate of negative laparotomy? Analysis of 3863 cases from Turkey - Ilhan, Enver; Senlikci, Abdullah; Kızanoglu, Hale; Ustüner, Mehmet Akif; Vardar, Enver; Aykas, Ahmet; Yeldan, Eyup; Yildirim, Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction : Acute appendicitis is the most frequently observed disease requiring emergency surgery. The role of parasites in its pathogenesis has long been discussed. The signs of the parasitic infestations can mimic the signs of acute appendicitis. Therefore, it can cause a negative laparotomy. Aim : To evaluate the parasitic infestations of the appendix vermiformis whether increas the rate of negative laparotomy. Material and methods : The histopathology results of a total of 3863 patients who underwent appendectomy with clinically acute appendicitis were evaluated retrospectively. All appendectomy materials in which parasites were observed were evaluated with respect to the nature of the parasites and the findings of inflammation. Cases in which parasite tissue fragments and/or eggs as well as findings of inflammation were histopathologically observed in the appendix lumen were diagnosed with parasitic appendicitis. Results : Evidence of parasites was observed in 19 (0.49%) of the evaluated appendectomy materials. In 9 (47.3%) of these specimens that had evidence for parasites, findings for acute appendicitis and localized peritonitis were identified. Findings of acute appendicitis had not been identified in the other ten (52.7%) of the specimens. Enterobius vermicularis was the most frequently identified parasite. Conclusions : In parasitic acute appendicitis, appendectomy in itself is not sufficient for treatment. Pharmacological treatment should also be administered after surgery. Patients should be evaluated prior to surgery for parasites, and diagnosis of acute appendicitis should be considered more cautiously in order to avoid negative laparotomies.